Interest of the BLAST paradigm and salivary markers for the evaluation of sleepiness in drivers - Thieux, Marine; Guyon, Aurore; Herbillon, Vania; Merle, Lydie; Lachaux, Jean-Philippe; Plancoulaine, Sabine; Seugnet, Laurent; Franco, Patricia (Frontiers in Neuroscience, 2022)
Objectives: Sleepiness is associated with decreased cognitive abilities and remains one of the main causes of fatal road accidents. The tools currently available to assess sleepiness, such as questionnaires, are subject to intra- and inter-individual variability, while multiple sleep latency tests are only feasible in few sleep laboratories. The main objective of this study was to explore new potential markers (neurocognitive, biological) to objectively assess sleepiness in drivers. Methods: A total of 186 drivers (median age 44 years, range 20-74 years, 73% men, 14% obese) were included during a break at a highway service area, in the morning, while on the road for vacation. Questionnaires on sleepiness and sleep characteristics (habitual and on the night before travel), the Bron-Lyon Attention Stability Test (BLAST), and two salivary samples (α-amylase and oxalate) were collected. Associations between measures of sleepiness (Epworth Sleepiness Scale (ESS), and Stanford Sleepiness Scale (SSS)), sleep characteristics, neurocognitive, and biological markers were tested using regression models adjusted for confounding factors. Results: The night before travel, 83% of the drivers reduced their sleep time and 30% slept 5 hours or less. The higher the number of miles to be traveled, the higher the decrease, and the shorter the sleep time. The night before travel, 18% and 24% of the drivers complained of poor sleep quality and difficulty falling asleep. The sleep characteristics on the night before travel were associated with the habitual sleep characteristics. At the time of the test, 47% of the drivers scored pathologically on the SSS. Poor sleep quality and difficulty falling asleep the night before travel were associated with increased sleepiness as assessed by the SSS and decreased attentional ability as assessed by the BLAST. No association between salivary markers and acute sleepiness was observed. Conclusions: The sleep characteristics of the night before travel were associated with sleepiness and attentional performance. The SSS and the BLAST could be used by individual drivers in a self-evaluation context. Biological markers showed a high variability and limited association with sleep parameters across subjects, emphasizing the need for within-subject designs to assess their usefulness.